A Molecular Barium Hydrido Complex Stabilized by a Super‐Bulky Hydrotris(pyrazolyl)borate Ligand. Issue 52 (5th December 2017) - Shi, Xianghui; Hou, Cuiping; Zhou, Chulu; Song, Yanyao; Cheng, Jianhua
Abstract: Hydrogenolysis of the scorpionate‐supported barium alkyl complex (Tp Ad, iPr )Ba[CH(SiMe3 )2 ](THF) (Tp Ad